Republican women : feminism and conservatism from suffrage through the rise of the new right - Rymph, Catherine E. (Gender & American culture., 2006)
Explores the dilemmas confronting progressive, conservative, and moderate Republican women as they sought to achieve a voice for themselves within the Grand Old Party (GOP). This book examines women's grassroots organizing for the party, in the decades following the initiation of women's suffrage.